Cross-section calculations for electron scattering from ketene in low energies using R-matrix method. (26th June 2015) - Wang, Kedong; Meng, Ju; Liu, Yufang; Sun, Jinfeng
Abstract: We report on a computational investigation of electron scattering by ketene in the correlated and uncorrelated approximations using the R -matrix method for energies ranging from 0 to 10 eV. The target wave functions are based on different-size basis sets and are tested to obtain the reliable properties of electronic states for the ketene molecule. The calculated elastic integral cross sections present two low-lying π * shape resonances belonging to 2 B 1 and 2 B 2 symmetries. Two higher-lying resonances of 2 B 1 symmetry, one core-excited shape resonance and one Feshbach resonance, are detected in the excitation cross sections. These resonances are in agreement with the available data in the literature. The Born correction is used to obtain converged cross sections for the L > 4 partial waves excluded from the R -matrix calculations. We compare the elastic cross sections with the available data for CO2 . The effective collision frequencies over a wide electron temperature range (100–30 000 K) are calculated using the data of the momentum-transfer cross section.